The Influence of Brand Equity on Repurchase Intentions for Scarlett Products in Border Regions - Deasi, Meriana; Kristianto, Aloysius Hari (ProBisnis : Jurnal Manajemen, 2024)
This study aims to analyze the effect of brand equity dimensions on repurchase intention of Scarlett skincare products in Bengkayang. The dimensions of brand equity studied include brand awareness, brand association, perceived quality, brand loyalty, and other brand assets such as product distribution channels. This research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to consumers who have used Scarlett products at least once. There are 200 respondents who have participated to fill out the questionnaire, but only 159 respondents were distributed in this study. The results showed that the variables of brand association, brand loyalty and other brand assets have a positive and significant influence on repurchase intention. In contrast, the variables of brand awareness and perceived quality show a negative and significant effect. These results indicate that good management of the dimensions of brand equity can increase consumer repurchase interest in Scarlett products. This study suggests adding other variables in future research to gain a deeper understanding.